Indeterminacy, Causality, and the Foundations of Monetary Policy Analysis - Bennett T. McCallum (Swiss Journal of Economics and Statistics, 2010)
To be useful as a guide to behavior, a model that includes a relationship between x_t and z_t+1 must specify whether x_t is influenced by the expectation at t of z_t+1 or, that z_t+1 is inertially influenced by x_t. We show that, for a broad class of linear RE models, distinct causal specifications will be uniquely associated with distinct solutions. Alternatively, a solution refinement requiring continuity of solution coefficients with respect to basic parameters implies this same solution. For a given structure there is only one RE solution that is fully consistent with the model's specification.
Keywords: E4; E5; E52; 330; determinacy; learnability; causality; continuity